(untitled) (Al-Qamar, 2024)
This study investigates at how Pakistan’s blasphemy laws are enforced, with particular focus on cases heard by the “Anti-Terrorism Court (ATC) in Lahore”. The research paper investigates the court’s rulings, trials, and higher-level implications for the legal system. The study aims to shed light on the challenges faced in deciding blasphemy cases in a specialized court environment by examining seven noteworthy cases. In accordance to the findings, modifications must be made to ensure fair trials and stop these laws from being exploited. Strengthening legal protections, fostering court education, and boosting understanding are some proposals for striking a balance between ensuring foundational human rights and safeguarding beliefs. The research study concludes by addressing the critical requirement for a thoughtful approach to blasphemy law execution and advocating a legal framework which upholds both human rights and religious holiness.